2022
DOI: 10.3390/molecules27123900
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Organic Reactions Involving Hypervalent Iodine Reagents

Abstract: The chemistry of polyvalent iodine compounds has piqued the interest of researchers due to their role as important and flexible reagents in synthetic organic chemistry, resulting in a broad variety of useful organic molecules. These chemicals have potential uses in various functionalization procedures due to their non-toxic and environmentally friendly properties. As they are also strong electrophiles and potent oxidizing agents, the use of hypervalent iodine reagents in palladium-catalyzed transformations has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…[80] An atom-efficient one-pot synthesis of novel push-pull dienaminodiones (12) was disclosed by Lankalapalli and his group, using indoles (9) and a Schiff base generated from 3,4dihydroxysalicylaldehyde (10) in the presence of PIDA (Scheme 1). [81] A wide range of indoles and anilines (11) made up the broad substrate scope of the methodology with good to moderate yields. The proposed approach functioned as a sequential multicomponent reaction since the formation of Schiff base was followed by an addition of indole to produce dienaminodione in one-pot.…”
Section: Cà C Bond Formationmentioning
confidence: 99%
“…[80] An atom-efficient one-pot synthesis of novel push-pull dienaminodiones (12) was disclosed by Lankalapalli and his group, using indoles (9) and a Schiff base generated from 3,4dihydroxysalicylaldehyde (10) in the presence of PIDA (Scheme 1). [81] A wide range of indoles and anilines (11) made up the broad substrate scope of the methodology with good to moderate yields. The proposed approach functioned as a sequential multicomponent reaction since the formation of Schiff base was followed by an addition of indole to produce dienaminodione in one-pot.…”
Section: Cà C Bond Formationmentioning
confidence: 99%
“…16–19 In addition, a serious problem associated with transition-metal-promoted reaction is the product contamination, which is not observed with iodine( iii / v ) reagents. Therefore, hypervalent iodine compounds are potential rivals to transition metals in many organic reactions as covered in several excellent review articles, 20–30 book chapters, and books. 31–39…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In addition, a serious problem associated with transition-metal-promoted reaction is the product contamination, which is not observed with iodine(III/V) reagents. Therefore, hypervalent iodine compounds are potential rivals to transition metals in many organic reactions as covered in several excellent review articles, [20][21][22][23][24][25][26][27][28][29][30] book chapters, and books. [31][32][33][34][35][36][37][38][39] Traditionaly, hypervalent iodine reagents are employed as stoichiometric reagents but recent studies have revealed their use as versatile catalysts, as reviewed by Singh, Wirth, and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…After that, especially within the last ten years, a variety of protocols for synthesis of these molecules have been developed and refined by researchers. Moreover, the palladium catalyst was also used extensively in cross-coupling reactions, such as Buchwald-Hartwig, Suzuki-Miyaura, Heck, Sonogashira, Negishi, and Stille to synthesize a variety of useful compounds [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%